The complexity science problem-based learning: Correlation of science literacy and concept mastery to problem-solving skills - Intan Nurnilam Sari; Susriyati Mahanal; Sitoresmi Prabaningtyas (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
Science and technology are rapidly developing in the 21st century which requires educators to facilitate real-life problem-based learning activities and the application of science that can stimulate problem-solving skills with science considerations. This research aims to determine the correlation of science literacy and concept understanding with students' problem solving skills and variables that are more influential in improving problem solving skills. The research sample consisted of 34 students of eleventh class of State Senior High School (SSHS) 6 of Malang who took Biology as an elective subjects. The variables measured in this study, namely predictor variables (science literacy and concept understanding), and criterion variables (problem solving skills). The data of the three variables were obtained from an essay test at the end of the lesson and then analyzed using multiple linear regression test. The results showed that the predictor variables (science literacy and concept mastery) gave a relative contribution to problem solving skills with a percentage of 72.1% and 27.9%, respectively. Science literacy variable is more influential on improving problem solving skills than concept mastery. The results of this study indicate a positive correlation between science literacy and concept understanding with problem solving skills.